Intervensi Supportive Educative Berbasis Caring Meningkatkan Self Care Management Penderita Hipertensi - Suprayitno, Emdat; Damayanti, Cory Nelia (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Hypertension is a major risk factor for cardiovascular disease death, derived from genetic, environmental,and social factors. Intervention strategies are urgently needed to increase awareness and self-care. Thepurpose of this study was to analyze the effect of a caring-based supportive educative intervention on selfcare management of hypertensive sufferers. This research design is quasi-experimental. The population was71 elderly people with hypertension with simple random sampling, 66 samples were divided into 2 groups,namely the treatment group as many as 33 people who were given caring-based supportive educativeintervention, and as many as 33 control groups were given leaflets about hypertension. The results of thestudy were based on the independent t-test score of self care management in the treatment and controlgroups after the intervention, namely p = 0.000. The difference in the delta score of self care managementscores in the treatment and control groups after the intervention is p = 0.000. The results of this studyindicate that caring-based supportive educative interventions are effective in improving self-caremanagement of hypertensive patients, this intervention can be a promotional effort to increase self-careindependence in hypertensive sufferers.